Metody mierzenia wartości dla klienta a efektywność koncepcji CRM w przedsiębiorstwie - Kąpa-Kejna, Krystyna (The Appreciation of Efficiency the Methods of Customer Value Measurement in CRM, 2005)
This elaborate presents complex issues of creating and measurement consumer value in an enterprise. It also shows the meaning of category of consumer value to create the value of an enterprise. Systematic analyses of customers satisfaction, gaining loyalty and creating consumer value ensure long-term competition supremacy of the market. Moreover it contribute to the growth of the value of an enterprise
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 218-228